The Loss of the Inverted Repeat in the Putranjivoid Clade of Malpighiales - Jin, Dong-Min; Wicke, Susann; Gan, Lu; Yang, Jun-Bo; Jin, Jian-Jun; Yi, Ting-Shuang (Frontiers in Plant Science, 2020)
The typical plastid genome (plastome) of photosynthetic angiosperms comprises a pair of Inverted Repeat regions (IRs), which separate a Large Single Copy region (LSC) from a Small Single Copy region (SSC). The independent losses of IRs have been documented in only a few distinct plant lineages. The majority of these taxa show uncommonly high levels of plastome structural variations, while a few have otherwise conserved plastomes. For a better understanding of the function of IRs in stabilizing plastome structure, more taxa that have lost IRs need to be investigated. We analyzed the plastomes of eight species from two genera of the putranjivoid clade of Malpighiales using Illumina paired-end sequencing, the de novo assembly strategy GetOrganelle, as well as a combination of two annotation methods. We found that all eight plastomes of the putranjivoid clade have lost their IRB, representing the fifth case of IR loss within autotrophic angiosperms. Coinciding with the loss of the IR, plastomes of the putranjivoid clade have experienced significant structural variations including gene and intron losses, multiple large inversions, as well as the translocation and duplication of plastome segments. However, Balanopaceae, one of the close relatives of the putranjivoid clade, exhibit a relatively conserved plastome organization with canonical IRs. Our results corroborate earlier reports that the IR loss and additional structural reorganizations are closely linked, hinting at a shared mechanism that underpins structural disturbances.